DESAIN PROTOTYPE UJIAN ONLINE BERBASIS WEB MENGGUNAKAN PHP MySQL UNTUK SISWA SMP - Ikhsan, Muhammad; Adhiatma, Novri (FORTECH (Journal of Information Technology), 2019)
The implementation of the School Examination is conducted to measure student achievement on competencies and achievements every year. The exam using Information Technology is felt today to have changed the exam system from manual to online exam. The examination process in SMP N 20 Jambi City is still manual, where the teacher gives the examination sheet to the exam committee. The examining committee shares to students then the students work on the specified time. The assessment is audited manually after the answer sheet is filled in by students which is usually done by the teachers, so that in the process of determining and disseminating the assessment is relatively long. By replacing the online-based exam system using the MySQL PHP Web, it is expected to be truly effective because all processes starting from submission of questions, tests and corrections are done online.